Webinar Recording: Professionalism on the Front line - Timms, Olinda (Research and Humanities in Medical Education, 2020)
https://www.youtube.com/watch?v=TmalDhX6VZw&feature=youtu.be Click to access a recording of the Webinar on YouTube.